Media interview techniques a complete guide to media training - Taylor, Robert 1968- (Kogan Page, 2016)
"A practical guide to preparing for, conducting, and evaluating the success of media interviews, this book is based on communications expert Robert Taylor's eight-step methodology for polished and confident interview delivery across a range of platforms--TV, radio, internet, and video. Taylor explains how to handle nerves, voice and body language, communicate in a crisis, answer unfair questions, know when to decline interviews, win over skeptical audiences, and create a resonant message"--Provided by publisher.